Smart Trends in Information Technology and Computer Communications First International Conference, SmartCom 2016, Jaipur, India, August 6-7, 2016, Revised Selected Papers - Unal, Aynur; Nayak, Malaya; Mishra, Durgesh Kumar; Singh, Dharm; Joshi, Amit (Communications in Computer and Information Science, 2016)
This book constitutes the refereed proceedings of the First International Conference on Smart Trends in Information Technology and Computer Communications, SmartCom 2016, held in Jaipur, India, in August 2016. The 106 revised papers presented were carefully reviewed and selected from 469 submissions. The papers address issues on smart and secure systems; technologies for digital world; data centric approaches; applications for e-agriculture and e-health; products and IT innovations; research for knowledge computing.